1995
DOI: 10.1002/j.1460-2075.1995.tb00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the binding site for inositol phosphates in a PH domain.

Abstract: Phosphatidylinositol bisphosphate has been found to bind specifically to pleckstrin homology (PH) domains that are commonly present in signalling proteins but also found in cytoskeleton. We have studied the complexes of the beta‐spectrin PH domain and soluble inositol phosphates using both circular dichroism and nuclear magnetic resonance spectroscopy, and X‐ray crystallography. The specific binding site is located in the centre of a positively charged surface patch of the domain. The presence of 4,5‐bisphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
335
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(352 citation statements)
references
References 39 publications
14
335
2
Order By: Relevance
“…These results with Tec are also consistent with a previous study of Bmx that found that the E42K mutant of Bmx has reduced kinase activity in fibroblasts (33). One possible explanation for the discrepancy between Btk and Tec/Bmx is apparent from models of other Tec kinase PH domain structures (46) based on the x-ray crystal structure of the Btk PH domain (54). Specifically, the glutamic acid residue at position 41 in Btk (42 in other Tec kinases) is thought to be too far away from the inositol-binding pocket to directly interact with the inositol phosphate moiety of phosphatidylinositol-3,4,5-trisphosphate (PtdInsP3).…”
Section: The Importance Of the Ph Domain In Tec Family Kinasessupporting
confidence: 90%
“…These results with Tec are also consistent with a previous study of Bmx that found that the E42K mutant of Bmx has reduced kinase activity in fibroblasts (33). One possible explanation for the discrepancy between Btk and Tec/Bmx is apparent from models of other Tec kinase PH domain structures (46) based on the x-ray crystal structure of the Btk PH domain (54). Specifically, the glutamic acid residue at position 41 in Btk (42 in other Tec kinases) is thought to be too far away from the inositol-binding pocket to directly interact with the inositol phosphate moiety of phosphatidylinositol-3,4,5-trisphosphate (PtdInsP3).…”
Section: The Importance Of the Ph Domain In Tec Family Kinasessupporting
confidence: 90%
“…The structure of several PH domains has been determined (Ferguson et al, 1994(Ferguson et al, , 1995Fushman et al, 1995;Hyvonen et al, 1995;Macias et al, 1994;Timm et al, 1994;Yoon et al, 1994). These structures exhibit a common globular fold that consists of seven anti-parallel b strands and an a helix (Gibson et al, 1994;Lemmon et al, 1996).…”
Section: A Structural Model Of the Akt Ph Domainmentioning
confidence: 99%
“…Our early studies, identifying Akt as a direct target of the PI3-K, showed that an Akt immunoprecipitate from lysates of serum-starved NIH3T3 cells was activated when incubated with D3 phosphorylated phosphoinositides (D3 PPIs) . Since the activation of Akt by PDGF requires an intact Akt pleckstrin homology (PH) domain and since PH domains bind phospholipids (Harlan et al, 1994;Hyvonen et al, 1995), these ®ndings suggested that Akt activation may depend on the binding of D3 PPIs to the Akt PH domain . This was con®rmed and extended by studies that examined the role of de®ned D3 PPIs in Akt activation.…”
Section: Introductionmentioning
confidence: 99%
“…The interacting counterpart is the WD40 repeats of the ␤ subunit of G-protein (20). More recently, several studies showed that various PH domains bind to phosphatidylinositol 4,5-bisphosphate (PIP 2 ) and inositol 1,4,5-trisphosphate (IP 3 ) through their positively charged residues in the amino-terminal four ␤-sheets (15,21,22). PIP 2 interactions with the amino-terminal PH domain of pleckstrin (21) and the PLC-␦1 PH domain (22) (30), and Txk/Rlk (31,32).…”
mentioning
confidence: 99%